Caracterización morfométrica y molecular de especies de anfibios y reptiles de la Estación Biológica José Álvarez Alonso, Loreto – Perú - Rios Alva, Ehiko Jerelhin (2023)
During the months of September and October 2021, we conducted sampling within the José Álvarez Alonso Biological Station using the technique of visual encounter surveys and molecular analysis in the installations of the Laboratory of Biology and Molecular Genetics, both belonging to the Peruvian Amazon Research Institute (Instituto de Investigaciones de la Amazonía Peruana). The main objective of this research was to characterize morphometrically and molecularly amphibian and reptile species of the EBJAA. We reported 153 individuals divided into 61 species between amphibians and reptiles, from which nucleotide sequences of the Cytochrome Oxidase - I gene were obtained from 81 individuals divided into 46 species. All individuals were measured at least with the snout-vent length, which helped us to determine which species would be used in the morphometric analysis. Preliminary Principal Component Analysis (PCA) only allowed us to perform morphometric characterization in three amphibian genera since the number of individuals per reptile species was not significant for statistical analysis. The analyses showed that snout-ventral length, head width and tibia length measurements could be used as morphometric characters for genus discrimination. Sequences of 20 species were added to the Genbank and the use of the combination of morphometric and molecular tools allowed us to correct the identification of the species Pristimantis brevicruz, Boana fasciata and B. tetete, which were misidentified. We conclude that the morphometric measurements used helped to find differential diagnostic characters, however, only using these characters does not ensure an adequate identification, so combining it with molecular analysis is necessary to obtain true and reliable data.